demoVLIZKULSSA.mp4 - Paolo Pilozzi (11628697) (2021)
This movie is part of a demonstration held at the Tech Demo Days organized by the Navy Belgium on October 1st, 2021. This was a joint effort between VLIZ and KU Leuven (Belgium), where VLIZ provided the Ademar (an autonomous surface vessel) and subsea sensor systems, and KU Leuven the technologies and back-end to enable Ademar to autonomously collect data from such sensor systems. This proof of concept yields a solution for VLIZ to collect data and diagnostics from their sensor systems installed around Greenland autonomously.